Analisis Potensi Hasil Fraksinasi Dari Ekstrak Etanol Daun Pacing (Costus spicatus (Jacq.) Sw.) sebagai Bahan Baku Obat Herbal terhadap Uji Aktivitas Pertumbuhan Rambut Kelinci - Sri Rezeki Samosir; Dina Maya Syari (Yayasan Literasi Sains Indonesia, 2025)
Hair growth disorders can be caused by many factors, one of which is oxidative stress and immunity, which can lead to baldness (alopecia). This study aims to analyze the potential of pacing leaf fractionation on rabbit hair growth. This research method is experimental in nature and conducted in a laboratory. The extraction stage uses the maceration method with 96% ethanol solvent for 3 days. The fractionation stage uses n-hexane and ethyl acetate solvents using a separating funnel. Based on the evaporation results, n-hexane fraction (FHE), ethyl acetate fraction (FEA), and ethanol fraction (FET) were obtained. Phytochemical tests for each fraction showed that FEA and FET contained flavonoids, alkaloids, tannins, saponins, and steroids/terpenoids. However, FHE only contained alkaloids and steroids. A total of 5 male rabbits were adapted and marked with 5 areas on their backs to be applied with FHE, FEA, and FET at a concentration of 50%, minoxidil 2% as K(+), and Na-CMC as K(-). Hair growth was observed for 28 days. The results showed that the activity of FET and FHE on day 28 resulted in good hair length, with an average hair growth of 2.22±0.101 mm and 2.15±0.064 mm for both fractions, and an average hair weight of 0.19±0.024 g and 0.19±0.015 g. Each fraction affected rabbit hair growth (p<0.05), The growth rate, FHE, FET, and K(+) did not differ significantly in terms of hair weight (p>0.05). However, the growth and hair weight results from minoxidil administration were still better than the overall fraction.